Validity and reliability of Turkish version of the scale on community care perceptions (Scope) for nursing students - BEYHAN, ABDULLAH; KADIOĞLU, HASİBE (My University, 2022)
Objective: The purpose of study was to conduct a study on validity and reliability of Turkish version of the “Community Care Perceptions for Nursing Students”. Methods: This methodological study was conducted in two of the universities located in Istanbul with 386 students between the dates May and December in 2019. During the designation of the Turkish version of the scale back-translation method was utilized for the language adaptation. Validity was assessed as content and construct validity and the reliability was assessed as internal consistency, test-retest analysis. Content validity was evaluated with expert views, construct validity with confirmatory factor analysis, internal consistency with Cronbach’s Alpha coefficient, test-retest results with Pearson’s Correlation analysis. Results: Cronbach’s Alpha coefficient was found as .94 and sub-dimensions ranged between .65-.88. Item total correlation was found over .20 excluding 26th, 28th items, test-retest correlation was calculated as .72. Content validity index was determined as .99. Confirmatory factor analysis was approved the structure of scale consisting of 33 items and 3 factors. Conclusions: Nursing Students’ Community Care Perceptions Scale was found to be valid and reliable. It may be used to assess community care perceptions of nursing students taking the course of community care nursing in Turkey.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Reviews and References (medical); Research and Theory; Community; perception; scale; nursing; HEALTH; VALIDATION; Community; perception; scale; nursing